26
$\begingroup$

Problem

Evaluate $$\lim\limits_{n\rightarrow \infty}\frac{n+n^2+n^3+\cdots +n^n}{1^n+2^n+3^n+\cdots +n^n}.$$

My solution

Notice that $$\lim_{n \to \infty}\frac{n+n^2+n^3+\cdots +n^n}{n^n}=\lim_{n \to \infty}\frac{n(n^n-1)}{(n-1)n^n}=\lim_{n \to \infty}\frac{1-\dfrac{1}{n^n}}{1-\dfrac{1}{n}}=1,$$and

$$\lim_{n \to \infty}\frac{1+2^n+3^n+\cdots+n^n}{n^n}=\frac{e}{e-1}.$$

Hence,\begin{align*}\lim\limits_{n\rightarrow \infty}\frac{n+n^2+n^3+\cdots +n^n}{1^n+2^n+3^n+\cdots +n^n}&=\lim_{n \to \infty}\frac{\dfrac{n+n^2+n^3+\cdots +n^n}{n^n}}{\dfrac{1+2^n+3^n+\cdots +n^n}{n^n}}\\&=\frac{\lim\limits_{n \to \infty}\dfrac{n+n^2+n^3+\cdots +n^n}{n^n}}{\lim\limits_{n \to \infty}\dfrac{1+2^n+3^n+\cdots +n^n}{n^n}}\\&=1-\frac{1}{e}.\end{align*}

The solution posted above need to quote an uncommon limit. Is there another more simple and more direct solution?

$\endgroup$
6
  • $\begingroup$ Wolfram alpha answer to the series is 1 wolframalpha.com/input/… $\endgroup$
    – emil
    May 23 '18 at 6:22
  • 7
    $\begingroup$ I'm afraid this's not true, though I don't know the reason for that. $\endgroup$ May 23 '18 at 6:52
  • $\begingroup$ The computer is not as smart as we are? $\endgroup$ May 23 '18 at 11:45
  • 5
    $\begingroup$ No, the computer is pretty dumb, though pretty fast. $\endgroup$ May 23 '18 at 11:57
  • 1
    $\begingroup$ Related: math.stackexchange.com/q/164074/321264. $\endgroup$ Mar 20 '20 at 13:20
9
$\begingroup$

We shall prove that $$ \frac{1^n+2^n+\cdots+n^n}{n^n}\to \frac{\mathrm{e}}{\mathrm{e}-1}\tag{$\star$} $$ First of all, $\log (1-x)<-x$, for all $x\in(0,1)$ and hence $$ \log\left(1-\frac{k}{n}\right)<-\frac{k}{n}\quad\Longrightarrow\quad \left(1-\frac{k}{n}\right)^n<\mathrm{e}^{-k}, \quad \text{for all $n>k$} $$ and thus $$ \frac{1^n+2^n+\cdots+n^n}{n^n}=\sum_{k=0}^{n-1}\left(1-\frac{k}{n}\right)^n <\sum_{k=0}^{n-1}\mathrm{e}^{-k}<\sum_{k=0}^{\infty}\mathrm{e}^{-k}=\frac{1}{1-\frac{1}{\mathrm{e}}}=\frac{\mathrm{e}}{\mathrm{e}-1}. $$ Hence $$ \limsup_{n\to\infty}\frac{1^n+2^n+\cdots+n^n}{n^n}\le \frac{\mathrm{e}}{\mathrm{e}-1}. \tag{1} $$

Meanwhile, for all $k\in\mathbb N$, $$ \frac{(n-k)^n}{n^n}=\left(1-\frac{k}{n}\right)^n\to\mathrm{e}^{-k}, $$ and hence, for every $k\in\mathbb N$ fixed, $$ \frac{1^n+2^n+\cdots+n^n}{n^n}\ge \frac{(n-k)^n+(n-k+1)^n+\cdots+n^n}{n^n}\\=\left(1-\frac{k}{n}\right)^n+\left(1-\frac{k-1}{n}\right)^n+\cdots+\left(1-\frac{1}{n}\right)^n+1\to \mathrm{e}^{-k} +\mathrm{e}^{-k+1}+\cdots+1=\frac{\mathrm{e}-\mathrm{e}^{-k}}{\mathrm{e-1}}. $$ Hence, for all $k\in\mathbb N$, $$ \liminf_{n\to\infty}\frac{1^n+2^n+\cdots+n^n}{n^n}\ge \frac{\mathrm{e}-\mathrm{e}^{-k}}{\mathrm{e-1}} $$ and thus $$ \liminf_{n\to\infty}\frac{1^n+2^n+\cdots+n^n}{n^n}\ge \sup_{k\in\mathbb N}\frac{\mathrm{e}-\mathrm{e}^{-k}}{\mathrm{e-1}}=\frac{\mathrm{e}}{\mathrm{e-1}} \tag{2} $$ Combining $(1)$ & $(2)$, we obtain $(\star)$.

$\endgroup$
5
$\begingroup$

I think the above sandwiching methods are only feasible when you already know the result before tackling the problem. I will present a method starting from scratch.

Note that for a special case of Faulhaber’s formula, the numerator equals $$S=\sum^n_{k=1}k^n=n^n\sum^n_{k=0}\frac{B^+_k}{k!}\frac{n!n^{1-k}}{(n-k+1)!}$$

It is well known that $$\frac{n!n^a}{(n+a)!}=1+o(\cdots)$$ as $n\to\infty$.

Thus, the required limit $$\frac{S}{n^n}\sim \sum^n_{k=0}\frac{B^+_k}{k!}=\frac1{1-e^{-1}}=\color{RED}{\frac{e}{e-1}}$$ by noting the generating function of Bernoulli numbers $$\frac{t}{1-e^{-t}}=\sum^\infty_{k=0}\frac{B^+_kt^k}{k!}$$

P.S.: I don’t know what the $o(\cdots)$ should be. Anyone who knows it please edit my answer.

Also, I don’t know how to type the symbol for asymptotic in Mathjax, please help me...

$\endgroup$
3
  • $\begingroup$ Symbol for asymptotics is, surprisingly, \asymp $\asymp$ $\endgroup$
    – Yuriy S
    May 24 '18 at 11:07
  • $\begingroup$ @YuriyS But can’t we type ‘~’? $\endgroup$
    – Szeto
    May 26 '18 at 0:12
  • $\begingroup$ @Szeto, try \approx. $\endgroup$ May 30 '18 at 5:14
3
$\begingroup$

A Query to @Teddy38's Answer

Yes, we can agree that $$n+n^2+\cdots+n^n=\frac{n}{n-1}(n^n-1)$$ and $$\frac{n^{n+1}}{n+1}=\int_{0}^{n}x^n\ dx<1^n+2^n+\cdots+n^n<\int_{1}^{n+1}x^n\ dx=\frac{(n+1)^{n+1}-1}{n+1}.$$ Thus,we obtain $$\frac{n+1}{n-1}\cdot \frac{n^{n+1}-n}{(n+1)^{n+1}-1}<\dfrac{n+n^2+n^3+\cdots +n^n}{1^n+2^n+3^n+\cdots +n^n}<\frac{n+1}{n-1}\cdot\frac{n^n-1}{n^n}.$$Now, let's evaluate the limits of the both sides as $n \to \infty.$ For the left side, we have $$\lim_{n \to \infty} \dfrac{n+1}{n-1} \cdot \lim_{n \to \infty}\dfrac{1-\dfrac{1}{n^n}}{\left(1+\dfrac{1}{n}\right)^n\cdot\left(1+\dfrac{1}{n}\right)-\dfrac{1}{n^{n+1}}}=\frac{1}{e}.$$ As for the right side, we have $$\lim_{n \to \infty} \dfrac{n+1}{n-1} \cdot \lim_{n \to \infty}\left(1-\dfrac{1}{n^n}\right)=1.$$

From the two aspects, we may only conclude that, $$\varliminf_{n\rightarrow \infty}\frac{n+n^2+n^3+\cdots +n^n}{1^n+2^n+3^n+\cdots +n^n}\geq\frac{1}{e},$$and $$\varlimsup_{n\rightarrow \infty}\frac{n+n^2+n^3+\cdots +n^n}{1^n+2^n+3^n+\cdots +n^n}\leq 1.$$ That's to say, if the limit we want really exists, then $$\frac{1}{e}\leq\lim\limits_{n\rightarrow \infty}\frac{n+n^2+n^3+\cdots +n^n}{1^n+2^n+3^n+\cdots +n^n} \leq 1.$$This is true, but can't give the accurate value of the limit we want.

$\endgroup$
2
  • $\begingroup$ Yup, my comment was too optimistic. I'll delete it. $\endgroup$
    – Teddy38
    May 24 '18 at 7:35
  • $\begingroup$ @Teddy38 It doesn't matter. Thanks for your participation in the discussion. $\endgroup$ May 24 '18 at 8:16

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.